Interaction of lncRNA-CR33942 with Dif/Dorsal Facilitates Antimicrobial Peptide Transcriptions and Enhances Drosophila Toll Immune Responses. - Zhou, H.; Li, S.; Pan, W.; Wu, S.; Ma, F.; Jin, P. (Journal of Immunology, 2022)
The Drosophila Toll signaling pathway mainly responds to Gram-positive (G+) bacteria or fungal infection, which is highly conserved with mammalian TLR signaling pathway. Although many positive and negative regulators involved in the immune response of the Toll pathway have been identified in Drosophila, the roles of long noncoding RNAs (lncRNAs) in Drosophila Toll immune responses are poorly understood to date. In this study, our results demonstrate that lncRNA-CR33942 is mainly expressed in the nucleus and upregulated after Micrococcus luteus infection. Especially, lncRNA-CR33942 not only modulates differential expressions of multiple antimicrobial peptide genes but also affects the Drosophila survival rate during response to G+ bacterial infection based on the transiently overexpressing and the knockdown lncRNA-CR33942 assays in vivo. Mechanically, lncRNA-CR33942 interacts with the NF-?B transcription factors Dorsal-related immunity factor/Dorsal to promote the transcriptions of antimicrobial peptides drosomycin and metchnikowin, thus enhancing Drosophila Toll immune responses. Taken together, this study identifies lncRNA-CR33942 as a positive regulator of Drosophila innate immune response to G+ bacterial infection to facilitate Toll signaling via interacting with Dorsal-related immunity factor/Dorsal. It would be helpful to reveal the roles of lncRNAs in Toll immune response in Drosophila and provide insights into animal innate immunity.